EFFECTS OF THE INQUIRY TRAINING AND MOTIVATION LEARNING AGAINST LEARNING OUTCOMES IN HIGH SCHOOL PHYSICS STUDENTS - Vika Andini (Universitas Negeri Medan, 2014)
This study aims to: determine the significance of differences in physics learning outcomes of students with learning models Inquiry Training and conventional models, knowing the significance of differences in physics learning outcomes of students who have learning motivation high and low, low motivation, the interaction model of learning and motivation to learn physics in improving student learning outcomes. The sample in this study conducted in a cluster random sampling of two classes, where the first class as a class experiment applied learning models and Inquiry Training as a second grade class learning model Conventional control applied. The instrument used in this study is the result of learning physics instruments in the form of 20 multiple-choice questions and motivation questionnaire by 25 statements has been declared valid and reliable. From the results of this study concluded that the learning outcomes of students who are taught by Training Inquiry learning model is better than conventional models of learning outcomes. Learning outcomes of students who have high motivation to learn is better than the learning outcomes of students who have a low learning motivation. Inquiry learning model training and motivation interact in affecting student learning outcomes.